Viability and functional recovery after chronic total occlusion percutaneous coronary intervention. Issue 5 (30th July 2021) - Schumacher, Stefan P.; Everaars, Henk; Stuijfzand, Wijnand J.; van Diemen, Pepijn A.; Driessen, Roel S.; Bom, Michiel J.; de Winter, Ruben W.; Somsen, Yvemarie B. O.; Huynh, Jennifer W.; van Loon, Ramon B.; van de Ven, Peter M.; van Rossum, Albert C.; et al.
Abstract: Objectives: This study evaluated myocardial viability as well as global and regional functional recovery after successful chronic coronary total occlusion (CTO) percutaneous coronary intervention (PCI) using sequential quantitative cardiac magnetic resonance (CMR) imaging. Background: The patient benefits of CTO PCI are being questioned. Methods: In a single high‐volume CTO PCI center patients were prospectively scheduled for CMR at baseline and 3 months after successful CTO PCI between 2013 and 2018. Segmental wall thickening (SWT) and percentage late gadolinium enhancement (LGE) were quantitatively measured per segment. Viability was defined as dysfunctional myocardium (<2.84 mm SWT) with no or limited scar (≤50% LGE). Results: A total of 132 patients were included. Improvement of left ventricular ejection fraction was modest after CTO PCI (from 48.1 ± 11.8 to 49.5 ± 12.1%, p  < 0.01). CTO segments with viability ( N  = 216, [31%]) demonstrated a significantly higher increase in SWT (0.80 ± 1.39 mm) compared to CTO segments with pre‐procedural preserved function ( N  = 456 [65%], 0.07 ± 1.43 mm, p  < 0.01) or extensive scar (LGE >50%, N  = 26 [4%], −0.08 ± 1.09 mm, p  < 0.01). Patients with ≥2 CTO segments viability showed more SWT increase in the CTO territory compared to patients with 0–1 segment viability (0.49 ± 0.93 vs. 0.12 ± 0.98 mm, p  = 0.03). Conclusions: Detection of dysfunctional myocardial segments without extensive scar (≤50% LGE) as a marker for viability on CMR aids in identifying patients with significant regional functional recovery after CTO PCI.